Biocatalytic Conversion of Cyclic Ketones Bearing α‐Quaternary Stereocenters into Lactones in an Enantioselective Radical Approach to Medium‐Sized Carbocycles. (5th March 2018) - Morrill, Charlotte; Jensen, Chantel; Just‐Baringo, Xavier; Grogan, Gideon; Turner, Nicholas J.; Procter, David J.
Abstract: Cyclic ketones bearing α‐quaternary stereocenters underwent efficient kinetic resolution using cyclohexanone monooxygenase (CHMO) from Acinetobacter calcoaceticus . Lactones possessing tetrasubstituted stereocenters were obtained with high enantioselectivity (up to >99 % ee ) and complete chemoselectivity. Preparative‐scale biotransformations were exploited in conjunction with a SmI2 ‐mediated cyclization process to access complex, enantiomerically enriched cycloheptan‐ and cycloctan‐1, 4‐diols. In a parallel approach to structurally distinct products, enantiomerically enriched ketones from the resolution with an α‐quaternary stereocenter were used in a SmI2 ‐mediated cyclization process to give cyclobutanol products (up to >99 % ee ).